Polimorfisme Lokus Mikrosatelit D10S1432 pada Populasi Monyet Ekor Panjang Di Sangeh - F. Rell; S.K. Widyastuti; I N. Wandia (Veterinary Science and Medicine Journal, 2013)
Genetic polymorphisms are variations in the genetic structure of populations that represents the base level of biodiversities.  This research aimed to assess the polymorphism of microsatellite locus of D10S1432 in the population of long-tailed macaques in Sangeh, Bali.  A total of 18 blood samples collected as a source of DNA. DNA was extracted using QIAmp® DNA Blood Mini Kit. Microsatellite locus was amplified by polymerase chain reaction technique (PCR) with a total of 30 cycles, and a 57oC of annealing temperature. Furthermore, the alleles were separated by 7% polyacrylamide gel electrophoresis, and emerged with silver staining. The results showed that there were three types of alleles found at D10S1432 locus in the long-tailed macaques population in Sangeh. The alleles size varied from 170 bp to 186 bp. The allele frequencies were  0.28, 0.67, and 0.05 for allele 170, allele 174, and allele 186 consecutively. The heterozygosity of the locus was 0.48. It can be concluded that microsatellites locus D10S1432 is polymorphic in the long-tailed macaques population in Sangeh.